Frontal assessment battery and frontal atrophy in amyotrophic lateral sclerosis. Issue 6 (12th April 2017) - Terada, Tatsuhiro; Miyata, Jun; Obi, Tomokazu; Kubota, Manabu; Yoshizumi, Miho; Yamazaki, Kinya; Mizoguchi, Kouichi; Murai, Toshiya
Abstract: Objectives: To determine the potential utility of the frontal assessment battery (FAB) in assessing cognitive impairments in amyotrophic lateral sclerosis (ALS), we investigated the association between the FAB score and regional gray matter volume, and ascertained whether the regional brain alterations related to cognitive impairments occur in relatively mild stage of ALS. Materials and Methods: Twenty‐four ALS patients with a Mini‐Mental State Examination score of >23, a normal score on the Self‐Rating Depression Scale, little or no disturbance in speech and handling utensils on the ALS Functional Rating Scale (ALSFRS), and normal measures on respiratory tests (respiratory function test and arterial blood gas analysis), and two age‐matched normal control groups (one for FAB assessment and the other for brain morphometry) underwent FAB testing and structural magnetic resonance imaging. We applied voxel‐based morphometry to investigate the relationship between the FAB score and regional brain alteration, and assessed the relationship between the altered regional brain volume and ALSFRS or respiratory tests. Results: Frontal assessment battery scores were significantly lower in ALS patients than in normal controls. Volume reduction in the right orbitofrontal gyrus in ALS was correlated with a lower FAB score. There was no correlation between the right orbitofrontal gyrus volume and ALSFRS or respiratory tests. Conclusions: The results suggest that the FAB is an adequate tool for detecting cognitive impairments related to frontal lobe pathology in the relatively mild stage of ALS, independent of physical dysfunctions. Abstract : The frontal cognitive impairments detected by the FAB are related to gray matter atrophy in the orbitofrontal gyrus even in patients with early‐stage ALS, and these associations are not due to motor impairment or respiratory failure.